Inconsistent Trafficking Obligations and How Guyana Got Caught In the Middle - Sarah Langer (Washington University Global Studies Law Review, 2018)
This Note will first analyze the mechanisms behind the enforcement of international trafficking laws and agreements which have, to a large extent, been disseminated by the United Nations and the United States. Specifically, this Note seeks to demonstrate how the use of sanctions by the United States, enacted in an effort to make adherence to international anti-trafficking norms compulsory, creates unpredictable standards for compliance and simultaneously disadvantages source countries. This Note will then look to anti-trafficking compliance in the Caribbean and specifically Guyana, to show why source and transition countries continue to struggle to meet international anti-trafficking goals. It will further demonstrate why the current legal framework, the enforcement of the Palermo Protocol through the Trafficking in Victims Protection Act, is not effective, and in fact undermines the goal of international collaboration.
Keywords: Trafficking; Guyana; Trafficking obligations; human trafficking; human rights